2021
DOI: 10.1080/13645579.2020.1857970
|View full text |Cite
|
Sign up to set email alerts
|

‘Working together is like a partnership of entangled knowledge’: exploring the sensitivities of doing participatory data analysis with people with learning disabilities

Abstract: The Open University's repository of research publications and other research outputs 'Working together is like a partnership of entangled knowledge': exploring the sensitivities of doing participatory data analysis with people with learning disabilities

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 25 publications
0
15
0
2
Order By: Relevance
“…Its grassroots activists advocate for the full autism spectrum (Kapp, 2020;Ne'eman & Pellicano, 2022), and likewise, value the contributions of people with intellectual disabilities to scholarship and society. Supported by the growth of the inclusive post-secondary education movement (Raynor et al, 2016) and participatory research (e.g., Chapko et al, 2020;Tilley et al, 2021), people with intellectual disabilities increasingly contribute to higher education and participatory research. The issue of the scope or boundaries of neurodivergence is important but relatively unexplored and demands future research on the views of people with neurological conditions (see Dwyer, 2022;Ne'eman & Pellicano 2022 for discussions on ethical considerations).…”
Section: Part 1: Neurodiversitymentioning
confidence: 99%
“…Its grassroots activists advocate for the full autism spectrum (Kapp, 2020;Ne'eman & Pellicano, 2022), and likewise, value the contributions of people with intellectual disabilities to scholarship and society. Supported by the growth of the inclusive post-secondary education movement (Raynor et al, 2016) and participatory research (e.g., Chapko et al, 2020;Tilley et al, 2021), people with intellectual disabilities increasingly contribute to higher education and participatory research. The issue of the scope or boundaries of neurodivergence is important but relatively unexplored and demands future research on the views of people with neurological conditions (see Dwyer, 2022;Ne'eman & Pellicano 2022 for discussions on ethical considerations).…”
Section: Part 1: Neurodiversitymentioning
confidence: 99%
“…Sue listened to these and suggested we work together to write about these history projects. In this way I became a published author (Tilley, Christian, et al, 2021; Tilley, Strnadová, et al, 2021).…”
Section: Setting the Scenementioning
confidence: 98%
“…Our review found that stages of analysis of photovoice data such as coding and synthesis was largely seen as the province of academic researchers. Involving people with intellectual disabilities in data analysis can be seen as a 'step too far' in inclusive research with people with intellectual disabilities (Nind, 2011), though more recently researchers have been developing and refining methods for addressing this (Tilley et al, 2021). More commonly researchers in the reviewed studies engaged in 'member checking' of the themes generated by researchers from photovoice data.…”
Section: Record and Reflect Community Concernsmentioning
confidence: 99%